2002
DOI: 10.1021/jp0142987
|View full text |Cite
|
Sign up to set email alerts
|

Conformational Control of Photoinduced Charge Separation within Phenothiazine−Pyrene Dyads

Abstract: Electron donor-acceptor systems, in which phenothiazine is tethered to pyrene by means of a phenyl bridge, exhibit a dual emission in moderately and very polar solvents. Employing steady-state and time-resolved fluorescence spectroscopy, we were able to provide evidence that the "blue" and "red" emission bands originate from different conformers. The ground-state geometry of the majority species is identical to that found in the crystalline state (the quasi-equatorial conformer). This conformation executes a f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
73
0

Year Published

2007
2007
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 87 publications
(77 citation statements)
references
References 67 publications
4
73
0
Order By: Relevance
“…A similar AIE behavior was also observed for PTZ-BP in THF/water mixtures (Figure 3b), whereas the only structural difference between the two compounds is that PTZ-XT contains an oxygen bridge, which Aggregation-induced delayed fluorescence N Aizawa et al restricts the internal rotations in the acceptor unit. Hence, the observed AIE behaviors of PTZ-XT and PTZ-BP are primarily attributed to aggregation-induced restriction of conformational changes in the phenothiazine donor unit [42][43][44] and the rotation around the single bond between the donor and acceptor units.…”
Section: Resultsmentioning
confidence: 99%
“…A similar AIE behavior was also observed for PTZ-BP in THF/water mixtures (Figure 3b), whereas the only structural difference between the two compounds is that PTZ-XT contains an oxygen bridge, which Aggregation-induced delayed fluorescence N Aizawa et al restricts the internal rotations in the acceptor unit. Hence, the observed AIE behaviors of PTZ-XT and PTZ-BP are primarily attributed to aggregation-induced restriction of conformational changes in the phenothiazine donor unit [42][43][44] and the rotation around the single bond between the donor and acceptor units.…”
Section: Resultsmentioning
confidence: 99%
“…1 for structural formula) [41,[64][65][66][67][68] and on the three subchromophores (BMF, PYM, PPT) of PYFPT [40,41,[61][62][63] allow an assignment on the energetic ordering of the frontier molecular orbitals (FMOs), namely highest occupied molecular orbital (HOMO) and lowest unoccupied molecular orbital (LUMO), as follows: E LUMO (phenothiazine) > E LUMO (pyrene) > E LUMO (flavin) and E HOMO (phenothiazine) > E HOMO (pyrene) > E HOMO (flavin). A qualitative energetic evaluation of the inter-component pathways via photo-induced electron transfer is delineated on the basis of the HOMO/LUMO schemata given in Figs.…”
Section: Discussionmentioning
confidence: 99%
“…The photo-dynamics of pyrene-phenothiazine with photo-induced charge-separation and conformational relaxation was studied in [64][65][66][67][68]. The photo-dynamics of a pyrene-flavine dyad and of a phenothiazine-flavin dyad were analysed in [63,69] and [62,69], respectively.…”
Section: Introductionmentioning
confidence: 99%
“…Many aromatic hydrocarbons may form charge transfer complexes in the excited states with amino acids which resemble aromatic amines upon excitation of their p-electronic systems [14][15][16][17][18][19]. Therefore, it is very important to know their interactions with biologically important molecules.…”
Section: Introductionmentioning
confidence: 99%
“…They are also used as oxygen sensors, DNA intercalators and solar cell components [37][38][39]. As mentioned earlier, functionalized Pyrene derivatives may have mechanical, optical or electrical properties that are different from those of Pyrene [17]. Our former studies on Pyrene and its derivatives have revealed that geometrical structures and molecular orbital energies are affected by the substituents and substitution positions in the Pyrene ring [21,40,41].…”
Section: Introductionmentioning
confidence: 99%